Legitimation technologies as factors of political mediation - Mykhailo Zienkin; Prymakov Kamil; Stavchenko Serhii; Vysotskyi Oleksandr (My University, 2025)
This study explores the critical role of legitimation technologies in enhancing the effectiveness of political mediation as a mechanism for achieving societal consensus, resolving conflicts, and ensuring the stability of governing structures. Political mediation operates within the public sphere, fostering dialogue between citizens, authorities, and institutions to negotiate power, influence, and social cohesion. Legitimacy serves as both a prerequisite and an outcome of successful political mediation, granting mediators the authority to facilitate agreements and ensuring the acceptance of outcomes by conflicting parties.
Keywords: political mediation; legitimation technologies; mythologization; symbolization; political communication; conflict resolution; political consensus; public sphere; legitimacy of power